Geography Teachers' In-Service Training Needs in Geography Teaching Program by Their Learning Areas - (:unkn) unknown (MARMARA UNIV, 2017)
In-service training, which people undergo throughout their professional lives, aims to increase the productivity of employees in their profession and can be realized in different forms in different occupational groups. The Ministry of National Education makes the greatest contribution to this development in the profession of teaching. As regards in-service training, it is extremely important that the objectives can be achieved in activities carried out in different branches of teaching or on topics involving general teaching knowledge. Determining, first and foremost, the needs and requests of teachers in this process, that is, carrying out needs analyses, plays an important role in achieving the goals. The purpose of this study is to determine the in-service training needs of the geography teachers depending on the five learning areas in the geography curriculum of the 9th, 10th, 11th and 12th grades of secondary education. The research was carried out in 2014-2015 education year with 210 geography teachers in Istanbul. The data were collected by the In-Service Training Needs Assessment Questionnaire prepared by the researchers. The collected data were evaluated by SPSS program and, frequency and percentage values were calculated. The results indicate that the topics for which the most in-service training is needed are: Assessing the regional and global impacts of a country's location (GIS), Ecosystem, Regional development projects in Turkey, The effects of human activities on carbon, nitrogen, oxygen and water cycles, and Biodiversity. In conclusion, it is thought that in-service training activities to be carried out in line with the findings of this study will be more beneficial to geography teachers.
Keywords: Geography; learning areas; in-service training; need determination